Analisis Kesalahan Mahasiswa dalam Geometri: Studi pada Pemahaman Sudut dalam Garis Sejajar - Annisa Saktiono; Agnia Kamila Rambe; Syifani Azzura; Jona Mikhael Hutagaol; Firman Satria Tafonao; Kms. Muhammad Amin Fauzi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the types of mistakes made by students in understanding the concept of angles on parallel lines and the factors that cause them. The approach used in this study is qualitative with a descriptive design, which allows the researcher to dig deeply into the pattern of errors that occur. The research subjects consisted of seven students who were selected using the purposive sampling technique based on certain criteria. Data collection is carried out through diagnostic tests that include various types of angles, such as facing angles, opposite inside corners, and unilateral inside angles. The results of the study show that student errors can be classified into four categories according to Soedjadi (in Ananda, dkk 2018), namely factual errors, conceptual errors, principle errors, and operational errors.